HYPERIDENTITIES OF LEFT AND RIGHT DISTRIBUTIVITIES IN VARIETIES OF SEMIGROUPS - Movsisian, Yu. M.; Simonian, I. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
An equality in a semigroup variety is called a superidentity if, substituting any term of the variety into the functional symbols of this equality, we obtain identities. Accordingly, an equality in a semigroup variety is called a presuperidentity if, substituting any term of the variety, excluding projection terms, we obtain identities into the functional symbols of this equality. In this paper, satisfiability criteria for superidentities and presuperidentities of left and right distributivities of various ranks were found.
Keywords: superidentity; presuperidentity; right distributivities; various ranks